PENGARUH STRATEGI PEMBELAJARAN EXPLICIT INSTRUCTION TERHADAP HASIL BELAJAR SISWA KELAS XI PADA MATA PELAJARAN 2 DIMENSI JURUSAN MULTIMEDIA SMKN 2 PADANG PANJANG - melda yanti (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
The low quality of student learning outcomes is influenced by the strategy delivered by the teacher that is not appropriate so that it has a major impact on student learning outcomes that are not optimal. For this reason, it is important that there is a breakthrough in the form of a strategy implemented by a teacher. The objectives of this research are; 1) To find out the learning outcomes of class XI students before and after the implementation of the Explicit Instruction Learning Model in the 2-dimensional subjects of the Multimedia Department at SMKN 2 Padang Panjang, 2) To determine the effect of the implementation of the Explicit Instruction Learning Model on student learning outcomes. The research method uses a quantitative approach. The data analysis technique used in this research is a quantitative research technique. By converting the scores into scores and using a t-test (paired sample test). The results in this study are explicit instructional learning strategies have a significant effect on student learning outcomes in class XI in the 2 Dimensional Subject of the Multimedia Department of SMKN 2 Padang Panjang. The application of the learning model with the explicit instruction strategy in the 2 Dimensional Subject of the Multimedia Department in the experimental class went well.